UMA ABORDAGEM SOBRE O ESPORTE: a história do esporte e sua função na escola como ferramenta de inclusão social - BALIEIRO, Mateus Pinto (2024)
This paper sought to understand sport as a factor of integration and social inclusion. Sport as a social phenomenon and the sphere of human activity play a growing role in the life of modern society. The growing contribution of sport has been instrumental in development and peace through tolerance and respect, the empowerment of the individual and the community, and the achievement of sport's goals of social inclusion. Sport for students with intellectual disabilities is educational and humanistic in nature and aims to develop the strengths, abilities and spiritual abilities that enable the athlete to overcome life's obstacles; the formation of character and moral responsibility in situations of adaptation to the social environment; provide opportunities for personal and professional growth for the implementation of athlete's self-fulfillment; creation of conditions for the self-development of the athlete's creative personality and dissemination of their creative potentials. The results presented in the article confirm that the presence of sport at school, in adaptive physical education, is educational, socializing and humanistic by nature and aims to develop strengths, abilities and spiritual skills that allow an athlete to overcome life's obstacles.